MENINGKATKAN KINERJA BISNIS PADA MASA COVID-19 - Surya Wijaya, Nyoman; Laksmita Dewi Rahmayanti, Putu; Made Darsana, I; Nengah Dasi Astawa, I (Berajah Journal, 2024)
This research aims to describe how innovation capabilities influence business performance by mediating the influence of Covid-19 risk perceptions. The sample in this research was 90 MSME managers in the Bali tourism and creative industry (parekraf), using a purposive sampling technique. The analysis approach uses Path Analysis with SEM-PLS. The findings show that there is a negative and significant impact on the influence of COVID-19 Risk Perception on business performance. Furthermore, there is a negative and significant impact between COVID-19 Risk Perception on Innovation Capability; Meanwhile, innovation ability has a positive and significant effect on business performance. The innovation capability in this research is able to mediate the influence of COVID-19 Risk Perception on business performance. Based on the research results, it is important for MSMEs in the tourism and creative sector in Bali to increase their innovation capabilities to improve business performance in facing the risk of the COVID-19 pandemic.